Nutritional Status, Physical Activity, and Sedentary Activity of School Children in Urban area, West Java, Indonesia - Yulia, Cica; Khomsan, Ali; Sukandar, Dadang; Riyadi, Hadi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2018)
The purpose of this research was to analyse nutritional status, physical activity, and sedentary activity in school children in West Java, Indonesia. The study used a cross-sectional design and was conducted from October to December 2016. Samples were taken using simple random sampling technique with a total sample of 300 subjects taken among fifth-grade students in seven elementary schools located in Bandung city, West Java. The data collected in this research were anthropometric data such as physical activity and sedentary activity. Data analysis was carried out using descriptive statistics, analysis of variance (ANOVA) and Pearson test. The results showed that 21.7% of school children were overweight, while 19.7% were obese. The results of the subject activity, based on nutritional status category, were not significantly different. All subjects with underweight nutritional status were having light activity (100%), the percentage of subjects with normal nutritional status, overweight, and obese were 71.6%, 75.4%, and 74.6%, respectively. The average duration of underweight subjects performing sedentary activities on holidays was 4.2±3.0 hours, 5.4±2.7 hours for normal subjects, 5.8±2.7 hours for overweight, and 5.4±2.5 hours for obese subjects. The proportion of sedentary activity time on holiday among underweight, normal, overweight, and obese subjects were 17.6±12.4%; 22.3±11%; 24.1±11.3%; and 22.3±10.5%. The sedentary activity of children on holiday was not significantly different, but there was a significant difference between the proportion of sedentary time in a day between groups of nutritional status (p<0.05), i.e., normal children and overweight children. The correlation test results indicated a negative correlation between physical activity and sedentary activity, meaning that higher sedentary activity of subjects both in school time and holiday resulted in lower physical activity (p<0.01). The nutritional status, physical activity, and subject sedentary activity based on nutritional status were not significantly different.